Utilization of Kapok Seed Oil (Ceiba pentandra) for Biodiesel Production using MgO/CaO Bimetallic Oxide Catalysts - Santoso, F. Agoes; Soe’eib, Siswanti; Suryandari, Ade Sonya; Asri, Nyoman Puspa (Proceedings of the International Conference on Green Technology, 2017)
The utilization of renewable energy resources received much attention due to the rapid depletion of fossil fuels. The production of biodiesel using homogeneous catalysts has several disadvantages such as complexity of separation process which leads the high production cost. Magnesium and calcium oxide (MgO/CaO) heterogeneous catalysts can be used to overcome these weaknesses. This study uses kapok seed oil ( Ceiba pentandra ) as the feedstock of biodiesel production. MgO/CaO catalysts were calcined at 950ᵒC for 5 hours. The catalyst activities were studied in various composition of MgO (0.5-2 wt.%) to determine the highest activity. The transesterification was carried out in various temperature (50-70ᵒC) in batch reactor. The highest yield was achieved for 0.5 wt.% of MgO composition in the catalyst with the yield of 59.58%. In the effect of temperature and reaction time study, the highest yield of 55.22% was achieved at temperature of 70ᵒC for 75 minutes.